Exploring Opportunities and Challenges in Multi-Cloud and Hybrid Cloud Implementation - Firdaus, Wigananda; Sukmaaji, Anjik (Information Technology International Journal, 2024)
This study reviews the opportunities and challenges of implementing Multi-Cloud and Hybrid Cloud models that focus on security and data management. Multi-Cloud implementation offers flexibility, but also brings challenges related to security and privacy. Data security in multi-cloud can be improved by implementing encryption such as Homomorphic Encryption and Hybrid Crypto which combines DES and RSA algorithms. The Hybrid Cloud model allows integration between public and private clouds. where the implementation of Zero Trus can improve the security of the cloud network. The results of this Literature Review emphasize the importance of security policies at every layer of the cloud from infrastructure to applications. this is done to protect sensitive data in the cloud environment. of course, the right strategy is needed in cloud data management so that the implementation of cloud computing is more effective